Lightweight ECC Based Multifactor Authentication Protocol (LEMAP) for Device to Device Cellular Network - Rashad Mahmood, Saqib; Adnan Shahid, Khan (Unimas, 2022)
Device to Device (D2D) communication is a type of technology where two devices can communicate directly with each other without the need to contact Base Station or any central infrastructure. With emerging of Long Term Evaluation (LTE) and Fifth Generation (5G) technology, D2D has gained a lot of attention for communication between closely located mobile devices for offering high speed, energy efficiency, throughput, less delay, and efficient spectrum usage. D2D has changed recent wireless networks with new trends as D2D can play a vital role in sharing resources by load off the network in local areas by direct communication between devices and useful in natural disasters where BS is destroyed. D2D has revolutionized the direct communication as it is a basis for 5G network. D2D allows miniature devices like cell phone, tablets and radio devices to work as Non-Transparent Relays (NTR) where they can provide services as well as forward traffic, request services by direct communication without the need of Base Station (BS) or central network infrastructure. Multi-hop D2D can be used for peer-to-peer communication or even access to cellular networks. This concept of multihop D2D communication has introduced a number of issues and challenges that were not prevalent in traditional current cellular communication. One of the major issues in D2D is security that is required in D2D communication to transmit information securely over non secure channel. The major challenge when considering security is that current established security techniques cannot be modified as security-requiring devices are miniature with restricted processing and storage or are constrained by power and bandwidth issues. Another issue is that how devices can get secure mutual authentication for secure communication. To tackle these issues, a lightweight multifactor authentication scheme that allows multihop secure communication over open channel is designed called as Lightweight ECC based Multifactor Authentication Protocol (LEMAP) in multihop D2D communication. Formal analysis of scheme is performed using well known BAN Logic method which is used to check correctness of protocol. The formal analysis of LEMAP proves that it can mitigate replay attack, Man-in-the-Middle (MITM) attack, Rogue device attack, Denial of Service (DoS) attack, timestamp exploitation attack, impersonation attack and masquerading attack. LEMAP also achieves security requirements confidentiality, integrity, privacy, non-repudiation, secure mutual authentication and anonymity. The communication cost and computational overhead of benchmark protocols and the proposed scheme LEMAP are also calculated. The results show that LEMAP is 6%-28% percent stronger than the selected benchmark algorithms such as 2PAKEP, Chaotic based authentication and TwoFactor authentication protocol. Additionally, LEMAP provides additional security by using trust validation, double hashing, and reduced authentication overhead. Discrete logarithm analysis shows that LEMAP is more secure compared to current security algorithms or current security algos are used as attacks against LEMAP. LEMAP is a lightweight and flexible scheme which can be used in 5G as well as multihop D2D communication to provide secure communication environment. Keywords: D2D security, multihop D2D security, multi factor, light-weight security, ECC